Modified island flap for basal cell carcinoma of the nasal apex - Simona Kordeva; Georgi Tchernev (PAGEPress Publications, 2024)
An 80-year-old female presented with an atrophic lesion in the area of the nasal apex, dating for the past 5-6 years. The lesion had a superficial telangiectasias and a pearly edge, measuring 1 cm in diameter. The patient denies painful sunburns in the past. Previous history of basal cell carcinomas located on the temporal and sacral regions. [...]